2017
DOI: 10.5433/1679-0359.2017v38n1p175
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of lettuce produced by conventional and organic systems in farms of Londrina, PR

Abstract: The aims of this study were to evaluate the contamination of lettuce (Lactuca sativa), produced in Londrina, Paraná (PR), with total coliform, coliform at 45 °C, E. coli, and Salmonella spp.; and to determine the E. coli contamination of irrigation water used at the farms studied. Four farms were evaluated, of which three produced lettuce using a conventional system and one using an organic system. An evaluation of the production practices of the farms was also carried out. A total of 111 samples were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This finding was also supported by research by Niguma et al on four lettuce plantations in Londrina, Brazil, which showed that 1 (1.4%) of lettuce grown using conventional techniques contained Salmonella sp. In contrast, Salmonella sp was not detected on all organically grown lettuces (Niguma et al, 2017).…”
Section: Abstrakmentioning
confidence: 76%
“…This finding was also supported by research by Niguma et al on four lettuce plantations in Londrina, Brazil, which showed that 1 (1.4%) of lettuce grown using conventional techniques contained Salmonella sp. In contrast, Salmonella sp was not detected on all organically grown lettuces (Niguma et al, 2017).…”
Section: Abstrakmentioning
confidence: 76%
“…Thermotolerant coliform counts in the investigated water samples were mostly below the maximum acceptable limits, while most fertilizer samples (animal and vegetable) presented counts above the maximum established limits (ICMSF, 2015). Thus, good agricultural practices in the handling and use of water and fertilizer inputs seem to not have been followed on the investigated property, as following the Good Agricultural Practices (GAP) program results in low or absent counts of this group of organisms (NIGUMA et al, 2017). At the assessed property, vegetables are harvested and sold directly to the final consumer.…”
Section: Discussionmentioning
confidence: 99%